Assessment of the Global Integration Method on the parents’ perception of functional goals in children and adolescents with autism - Deisiane Oliveira Souto; Amanda Aparecida Alves Cunha Nascimento; Thalita Karla Flores Cruz; Arthur Felipe Barroso de Lima; Gabriela Silva Oliveira; Ana Clara Schaper Fernandes; Vitor Geraldi Haase (Dementia & Neuropsychologia)
ABSTRACT Children with autism spectrum disorder (ASD) may experience impairments across all domains of the International Classification of Functioning, Disability, and Health. However, there is a scarcity of programs that integrate interventions encompassing all these domains. Objective: To investigate parents’ perception of performance and satisfaction with functional goals for children with ASD after intervention with the Global Integration Methods: This single-group quasi-experimental study involved a total of 98 participants aged 1.8 to 18.2 years who underwent a 3-month intervention, five times a week, for 3-4 h per day. The intervention involved functional task training in an environment inspired by the natural environment associated with the use of a flexible therapeutic suit. The primary outcome measure was the Canadian Occupational Performance Measure, administered before and after the intervention. Results: Ninety-five participants completed the study. Approximately 60% of participants showed improvements in performance and satisfaction that ranged from 1 to 9 points on the Canadian Occupational Performance Measure. The Global Integration Method program resulted in significant improvements in goal performance (p<0.001, d=0.80) and satisfaction (p<0.001, d=0.67). Most parents (81%) believed that the Global Integration Method incorporated aspects of family-professional collaboration and were satisfied (93%) with the intervention. Conclusion: In the perception of parents, the Global Integration Method demonstrated effectiveness in achieving functional goals for children with ASD and their families. Parents expressed satisfaction with the intervention and indicated that it incorporated elements of family-professional collaboration.